Correlation between self-efficacy in treatment and rehabilitation programs with functional status among post-stroke patients - Pratiwi, Sri Hartati; Fitriani, Nur; Platini, Hesti (JOURNAL OF Mental Health Concerns, 2026)
Background: Stroke patients must comply with medication and undergo rehabilitation to prevent recurrent attacks. Self-efficacy plays a significant role in patient adherence to and compliance with these programs. Post-stroke patients have varying functional statuses, which may result in differences in their levels of self-efficacy in carrying out these programs. Purpose: To identify the relationship between patients' self-efficacy in undergoing rehabilitation and treatment. Method: A correlational descriptive study using accidental sampling conducted on 69 post-stroke patients. Data were collected using the Stroke Self-Efficacy Questionnaire (SSEQ), the Self-Efficacy for Appropriate Medication use Scale (SEAMS), and the Barthel Index. Data analysis was performed using Spearman's analysis. Results: Most respondents (40.6%) had high self-efficacy in rehabilitation, 62.3% had high self-efficacy in medication, and 56.5% had mild dependence. There was a significant relationship between self-efficacy in carrying out rehabilitation and the functional status of patients (p = 0.000), and there was a significant relationship between self-efficacy in carrying out medication and the functional status of patients (p = 0.000). Conclusion: There is a significant relationship between self-efficacy in undergoing rehabilitation and treatment and the functional status of patients. Health workers, especially nurses, must motivate patients to undergo treatment and rehabilitation, particularly those with low functional status. Keywords: Functional Status; Rehabilitation; Self-Efficacy; Treatment.